2021
DOI: 10.2169/internalmedicine.6068-20
|View full text |Cite
|
Sign up to set email alerts
|

Noteworthy Cardiovascular Involvement with Sporadic Late-onset Nemaline Myopathy

Abstract: Cardiac involvement has recently been the focus of sporadic late-onset nemaline myopathy (SLONM). However, right ventricular failure and pulmonary hypertension, in addition to repetitive cardiac arrest, are noteworthy characteristics of SLONM. We herein report a 66-year-old woman with SLONM whose main symptoms were cardiac arrest, right ventricular failure, and pulmonary hypertension. Despite permanent pacemaker replacement, cardiac arrest occurred repetitively, and even with continuous positive airway pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…11 Mild involvement of facial and bulbar muscles was observed only in 1 and 3 individuals, respectively, which was less common than that of other reports. 11 Although several reports indicated that the pulmonary and cardiac involvement in SLONM was the leading cause of death, 10,17-19 none of our patients had subjective symptoms or objective evidence indicating cardiopulmonary dysfunction. Generally, a combination of myogenic changes with spontaneous activities on EMG examination is more common in necrotic myopathy, such as myositis or muscular dystrophy, in which the CK level is always remarkably elevated.…”
Section: Discussionmentioning
confidence: 59%
“…11 Mild involvement of facial and bulbar muscles was observed only in 1 and 3 individuals, respectively, which was less common than that of other reports. 11 Although several reports indicated that the pulmonary and cardiac involvement in SLONM was the leading cause of death, 10,17-19 none of our patients had subjective symptoms or objective evidence indicating cardiopulmonary dysfunction. Generally, a combination of myogenic changes with spontaneous activities on EMG examination is more common in necrotic myopathy, such as myositis or muscular dystrophy, in which the CK level is always remarkably elevated.…”
Section: Discussionmentioning
confidence: 59%